In Vitro Measurements of True Digestibility and Products of Digestion Using Multiple Cultivars of Non-Extracted and CBD-Extracted Industrial Hemp Biomass (Cannabis sativa) - Altman, A.W.; Vanzant, E.S.; McLeod, K.R.; Harmon, D.L. (Frontiers in Animal Science, 2022)
Since 2018, the growth of industrial hemp (Cannabis sativa) for extraction of cannabidiol oils (CBD) has increased in popularity. By-products resulting from the extraction of the oil have become more available but remain largely unutilized due to their novelty and current restrictions on animal feeding. One potential use for the leftover inflorescence may be as a feedstuff, but reports examining its nutrient quality are limited. Therefore, experiments were conducted to evaluate 9 cultivars of non-extracted and 9 separate cultivars of CBD-extracted foliage. Ground alfalfa cubes were included in experiments as a control. All samples were analyzed for ash, ether extract, crude protein, lignin, ash-free neutral detergent fiber, acid detergent insoluble crude protein, and neutral detergent insoluble crude protein. Total digestible nutrients (TDN) was calculated using summative equations. In vitro true digestibility (IVTD) was determined using a filter bag technique and 48h digestion period. Cumulative gas production was measured in batch culture over a 48h period, with methane and ammonia production, volatile fatty acid (VFA) formation, and dry matter disappearance (DMD) measured following this period. Substrates for gas production measurements were comprised of the hemp sample, rye silage, and ground corn mixed at a 30:35:35 ratio. Grind size (0.5mm vs 2.0mm) was evaluated using non-extracted hemp and did not influence IVTD (P = 0.79). Nutrient composition ranges of non- and CBD-extracted samples were similar, except for numerically higher mean ether extract (17.66% vs 9.29%) and TDN (73.01% vs 54.03%) in non-extracted hemp. None of the measured nutrients for alfalfa cubes fell within the observed concentration ranges of either hemp group, but TDN was similar to CBD-extracted hemp. IVTD was similar between both hemp groups and alfalfa cubes. In comparison to alfalfa cubes, VFA (both concentration and molar proportions), ammonia concentrations, pH, DMD, methane, and total gas production were similar with concurrently run non- and CBD-extracted hemp groups. The results of this study serve as a foundation from which a larger database of nutrient component values for hemp may be compiled. Such databases are necessary to fully evaluate the feasibility of a feedstuff for inclusion in animal diets.